Dynamic Response and Shear Mechanisms of Reinforced Concrete Columns Subjected to Lateral Impact - Zhihan Hou; Jiawen Xu; Jingming Sun; Fei Luo; Wangqiang Zhao (International Journal of Engineering and Technology Innovation, 2026)
This study investigates the dynamic response and shear failure mechanisms of reinforced concrete (RC) columns under lateral impacts, such as vehicle collisions. A three-dimensional nonlinear finite element (FE) model is developed, incorporating concrete damage, reinforcement plasticity, and strain-rate effects. The numerical model is validated against experimental pendulum impact tests. Parametric analyses are conducted to evaluate the effects of impact severity, axial compression ratio, stirrup ratio, longitudinal reinforcement ratio, slenderness ratio, and concrete strength on failure modes. Results indicate that impact-induced diagonal cracking governs the transition from non- failure to punching-shear failure. Increasing the stirrup ratio and concrete strength delays brittle shear failure, whereas excessive axial compression promotes shear localization. The findings provide insights into the impact-resistant behavior of RC columns and offer guidance for improving structural design against lateral impact loads.